Intestinal and Limb Ischemic Preconditioning Provides a Combined Protective Effect in the Late Phase, But not in the Early Phase, Against Intestinal Injury Induced by Intestinal Ischemia–Reperfusion in Rats. Issue 5 (May 2018) - Yang, Bo; Chen, Ye; Long, Yan-Hong; Fan, Xin; Liu, Ke-Xuan; Wang, Xiao-Bin; Zhou, Jun
Abstract : ABSTRACT: Intestinal ischemia/reperfusion (I/R) injury is associated with high morbidity and mortality. This study aimed to compare the protective efficacy of intestinal ischemic preconditioning (IIPC) and limb ischemic preconditioning (LIPC) against intestinal I/R injury and investigate their combined protective effect and the underlying mechanism. Male Sprague–Dawley rats were pretreated with IIPC, LIPC, or IIPC plus LIPC (combined), and intestinal I/R or sham operation was performed. The animals were sacrificed at 2 and 24 h after reperfusion and then blood and tissue samples were harvested for further analyses. In additional groups of animals, a 7-day survival study was conducted. The results showed that ischemic preconditioning (IPC) improved the survival rate and attenuated intestinal edema, injury, and apoptosis. IPC decreased the levels of tumor necrosis factor-α, interleukin -6, malondialdehyde and myeloperoxidase, and increased the activity of superoxide dismutase in serum and intestine after the I/R event. IPC downregulated the expression of Toll-like receptor-4 (TLR4) and nuclear factor-kappa B (NF-κB). The effect of combined pretreatment was better than that of single pretreatment in the late phase (24 h), but not in the early phase (2 h). The study demonstrated that IPC could significantly attenuate intestinal injury induced by intestinal I/R via inhibiting inflammation, oxidative stress, and apoptosis. IIPC and LIPC conferred no synergy in protecting I/R-induced intestinal injury in the early phase, but combined preconditioning had clearly stronger protection in the late phase, which was associated with the inhibition of the activated TLR4/NF-κB signaling pathway. It suggested that LIPC or combined preconditioning could potentially be applied in the clinical settings of surgical patient care.